Construction of Eu3+ Ion-Selective Electrode Based on 1,2-Diaminopropane-N,N,N',N'-tetraacetic acid - Mohammad Reza Abedi; Hassan Ali Zamani (E-Journal of Chemistry)
A new Eu3+ PVC membrane electrode based on 1,2-diaminopropane-N, N,N',N'-tetraacetic acid (DAPTA) as a suitable ionophore has been prepared and studied. The electrode shows a good selectivity for Eu(III) ion with respect to most common cations including alkali, alkaline earth, transition and heavy metal ions. This electrode has a wide linear dynamic range from 1.0×10-6 to 1.0×10-2 M with a Nernstian slope of 19.7±0.5 mV per decade and a low detection limit of 7.2×10-7 M in the pH range of 2.5–9.1, while the response time was rapid (<10 s). The practical utility of the electrodes has been demonstratedby their use as indicator electrodes in the potentiometric titration of Eu3+ ions with EDTA and for the determination of Eu3+ in some water sample solutions.